Migrantes en el estado de México: patrones migratorios diversos y formas de organización - Felipe González Ortiz (Universidad Autonoma del Estado de Mexico, 2005)
After some reflections about mexiquenses in the United States and their specific migratory phenomena, it is possible to detect three types of migrants: non-indigenous migrants, socialized in rural environments; non-indigenous migrants, socialized in urban environments; indigenous migrants, socialized in urban environments. This characterization allows us to establish a distinction in the specific forms of social organization and distinguish different migratory patterns. This work represents a first sight of the phenomena and a first systematic approach to international migration of population from the State of Mexico